Onset of normal cycles in postpartum anovulatory dairy cattle treated with kisspeptin - Chris R Burke; John R Roche; Robert P Millar; Iain J Clarke (Bioscientifica, 2022)
The efficacy of a long-acting synthetic derivative of kisspeptin (Kp) to initiate normal oestrous cycles was tested in 24 mixed-aged, Holstein-Friesian cows that were 18-25 days postpartum on the day of treatment (D0). Groups of eight cows received saline (Sal) vehicle by intramuscular injection at 8:00 and 16:00 h (Sal-Sal), Kp at 8:00 h and vehicle at 16:00 h (Kp-Sal) or Kp on both occasions (Kp-Kp). The Kp dose was 15 nmol per 60 kg body weight. The ovaries of the cows were examined daily by ultrasonography between D4 and D14. Blood samples were collected from a tail vessel at 0, 2, 4, 8, 10 and 12 h relative to the time of the first injection for luteinizing hormone (LH) and follicle-stimulating hormone assay. Additional samples were collected daily from D4 until D14 and D19, 22, 26 and 29 for progesterone assay. LH surge-like responses were observed in cows treated with Kp at 8:00 h. Ovulation was consistently induced by Kp within 48 h when a dominant ovarian follicle of at least 10 mm in diameter was observed (8/14) but in no cases (6/14) during a new wave of ovarian follicular development comprising follicles <10 mm in diameter. The subsequent ovulatory cycle was of normal length in most cases as compared with short 8- to 12-day cycles observed in spontaneously ovulating cows. We conclude that Kp treatment can induce ovulation in postpartum dairy cows, with ensuing oestrous cycles of normal length, if administered when a mature dominant follicle is present in the ovaries.